Cloning, genetic engineering and characterization of TMOF expressed in Saccharomyces cerevisiae to control larval mosquitoes. (April 2018) - Borovsky, Dov; Nauewelaers, Sabine; Powell, Charles A.; Shatters, Robert G.
Graphical abstract: Highlights: GFP-TMOF expression in S. cerevisiae. Homologues recombination. Larval control with recombinant S. cerevisiae-tmf A. Genetic engineering of S. cerevisiae. Abstract: Trypsin modulating oostatic factor, a decapaptide isolated from the ovaries of A. aegypti, is the physiological factor that terminates the trypsin biosynthesis after the blood meal. Earlier results obtained from feeding mosquito larvae and injecting female mosquitoes with TMOF show that trypsin biosynthesis and egg development are inhibited, indicating that TMOF traverses the gut epithelial cells and modulates trypsin biosynthesis, making it a potential larvacidal peptide hormone. Therefore, TMOF and TMOF green fluorescent protein (GFP) fusion protein with a trypsin cleavage site, allowing TMOF release in the larval gut, were expressed in S. cerevisiae cells that were transformed using homologous recombination at ura3-52 with an engineered plasmid (pYDB2) carrying tmf A and gfp-tmf A and a strong galactose promoter ( PGAL 1 ). Southern blot analyses showed that each cell incorporated a single tmf A or gfp-tmf A. Western blot analyses of cells that were fermented up to 48 h showed that the engineered S. cerevisiae cells synthesized both TMOF and GFP-TMOF and heat treatment did not affect the recombinant proteins. Engineered S. cerevisiae (3 × 10 8  cells) that were fermented for 4 h produced (2.1 ± 0.2 μg ± S.E.M) of TMOF. Feeding the engineered cells producing TMOF and GFP-TMOF to larval mosquito caused high mortalities (66 ± 12% and 83 ± 8%, respectively). S. cerevisiae cells transfected with pYEX-BX carrying gfp-tmf A and ( DPAR ) 4 or transformed by homologous recombination of pYDB2- gfp-tmf A carrying a heat shock promoter ( PHP ) were ineffective. Engineered heat treated yeast cells are consumed by mosquito larvae, and could be used to control mosquitoes.